Design of School Information System Using Waterfall Method (Case study: MTsN 8 Bantul) - Rovalia Adhella; Arizona Firdonsyah (Procedia of Engineering and Life Science, 2021)
The development of technology is now getting wider and starting to spread in various fields, one of the areas affected by the development of technology is education. This development has the intention of streamlining existing activities. The design of the school information system at MTsN 8 Bantul is to facilitate activities in data processing at the school. Using the waterfall method is expected to make it easier in this research, as well as telling, analyzing, and classifying problems as a supporting method. The result of this research is a school information system design.